Spongiform leukoencephalopathy unveiled in an autopsy of a drug abuser - Jangir, Hemlata; Balmuchu, Govinda; Mylapalli, Jhansi Lakshmi; Subramanian, Arulselvi; Lalwani, Sanjeev (Autopsy and Case Reports, 2024)
Toxic leukoencephalopathy (TLE) is a rare neurological debilitating and fatal condition. It has been previously associated with exposure to leukotoxic offenders such as chemotherapy, cranial radiation, certain drugs, and environmental factors. Currently, it is a commoner white matter syndrome resulting from increased substance abuse, classically by inhaled heroin and other opioids. Herein, we report a case of fatal TLE unveiled in an autopsy of a drug abuser. A 24-year-old male was found dead on the roadside. A day before, he was located in a state of delirium. In this case, the autopsy findings and histopathology characteristics of cerebral cortex involvement particularly directed to speculate the heroine as the principal offender.